2012
DOI: 10.5021/ad.2012.24.3.295
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy and Safety of 17α-Estradiol (Ell-Cranell® alpha 0.025%) Solution on Female Pattern Hair Loss: Single Center, Open-Label, Non-Comparative, Phase IV Study

Abstract: BackgroundThere are several commercially available agents to treat female pattern hair loss (FPHL), including minoxidil solution, anti-androgen agents and mineral supplements. However, these treatments are not always satisfactory. We report the results of a clinical trial of 17α-estradiol (Ell-Cranell® alpha 0.025%) solution to Korean female patients with FPHL.ObjectiveThis study was designed to examine the efficacy and safety of Ell-Cranell® alpha 0.025% solution in Korean female patients with FPHL.MethodsA t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…There is no evidence to support the use of topical natural oestrogens, progestogens or anti‐androgens in female AGA (level of evidence 4) …”
Section: Hormonesmentioning
confidence: 99%
“…There is no evidence to support the use of topical natural oestrogens, progestogens or anti‐androgens in female AGA (level of evidence 4) …”
Section: Hormonesmentioning
confidence: 99%
“…However, 17α-estradiol does not exhibit estrogen activity or exhibit only very weak activity181920. Kim et al21 reported that the hair count and thickness steadily increased after application of topical 17α estradiol when compared with the baseline.…”
Section: Discussionmentioning
confidence: 99%
“…34 In a clinical trial, topical application of alfatradiol solution exhibited statistically significant increase in number of hair and diameter from baseline; and hair improvement in self-assessment and global photographic assessment compared with placebo treatment. 35 Additionally in a separate clinical study, alfatradiol after topical application showed reduction or stabilization of hair loss.…”
Section: Emerging Agents With Potential In Treatment Of Aga Alfatradiolmentioning
confidence: 99%